CHURCH, STATE AND MIND CONTROL IN COSTA RICA: THE CASE OF THE PROHIBITION OF THE TEACHING OF THEOSOPHY IN THE COLEGIO SUPERIOR DE SEÑORITAS (1922) - Urbina Gaitán, Chester (2016)
The conflict between State and Church derived from the “alleged” teaching of Theosophyin the Colegio Superior de Señoritas is linked to the interest of the church to teach thereligious instruction mandatorily and increase its mental power. This situation led to anintense frontal journalistic debate in when the Church is urged help out the poor, it iscensored confessional character of the Costa Rican State and its negative impact on thefreedom of conscience. Also, the Church is criticized for not to combat materialism, notto promote the women’s equality, the sale of liquor in communal celebrations, the livingout of the priests through the work of others and the absence of support the protectionof animals.